Exploring the Influence of Planting Densities and Mulching Types on Photosynthetic Activity, Antioxidant Enzymes, and Chlorophyll Content and Their Relationship to Yield of Maize - Li Zhao; Chang Zhang; Min Liang; Pei Chen; Sumera Anwar; Mingyuan Fan; Guangming Xie; Chuangyun Wang (Plants)
High-density maize cultivation can enhance yield, but water scarcity on the Loess Plateau may limit this potential. Mulching is a sustainable practice that conserves soil moisture, yet limited studies exist on the combined effects of planting densities and mulching types on maize performance in this region. Over two years, an experiment investigated the effects of mulching (no mulching (NM), plastic film mulching (PM), and straw mulching (SM)) at various densities (60,000 to 90,000 plants ha−1). The results showed that mulching significantly improved grain yield and other metrics compared to NM. PM and SM enhanced yields notably at 75,000 plants ha−1, while NM was more favorable at 67,500 plants ha−1. Physiological responses varied with density, showing a decreased photosynthesis rate alongside an increased transpiration rate. PM exhibited a 32 and 13% increase in catalase and superoxide dismutase activities, while malondialdehyde content was reduced by 7% compared to NM. The average of both years indicates that PM significantly increased the grain yield, net photosynthesis rate, and chlorophyll content by 5.8, 26.8, and 26.9%, while SM showed a 3, 12, and 12% increase, respectively, compared to NM. In conclusion, the combination of mulching and optimized planting density could enhance maize cultivation in the Loess Plateau.